Teacher Strategy for Realizing the Religious Culture of Students at Satit Phatnawitya School Yala Thailand - Nabila; Abd Rahman (STIT Sirojul Falah Bogor, 2025)
Moral decline and uneducated behavior from students is an inevitable challenge in the world of education. Akhlakul Karimah character can be created through religious culture in the school environment. Teachers as a superior sector, role models and role models for students have an important role in internalizing this religious culture. This research is qualitative research with a descriptive approach. Using observation, interviews, and documentation as data collection methods. The data source comes from interviews with the head of the institution and four teachers. Data analysis uses an interactive model, namely through the process of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the strategies adopted by teachers to realize students' religious culture are cultivating the 6S (Senyum, Salam, Salim, Sapa, Sopan, Santun), getting used to praying together before and after studying, muroja'ah short surahs, reading and memorizing Al Quran, getting used to shalat together, turning on sholawat chants, watching the story of Nabiyullah, decorating the classroom walls with calligraphy, hijaiyah letters, and Islamic nuances, cultivating an attitude of mutual tolerance and mutual respect, getting used to saying bismillah, alhamdulillah, Masha Allah, Subhanallah, Allahu Akbar, and muroja'ah Surah Al Kahf. Supporting factors for the realization of students' religious culture are students' internal motivation, school policy on conducting study tours, exemplary teacher, adequate school facilities and infrastructure, and the establishment of cooperation between teachers and teachers, teachers and parents, teachers and students. Meanwhile, the inhibiting factor for the realization of students' religious culture is that students come from different regions.